IMPROVEMENT OF LOCAL AREA GOVERNING: THE NATURE OF INFORMATION UNCERTAINTY IN CASE OF EVALUATION OF EXECUTIVE POWER BODY OPERATION - O. Yu. Saveliev (Модернизация, инновация, развитие, 2015)
The article describes the analysis of the nature of uncertainty caused by information quality.